Analisis Limbah Medis Layanan Kesehatan Gigi Mandiri dan Potensi Pencemarannya di Kota Pekanbaru - Oktavia Dewi; Sukendi Sukendi; Yusni Ikhwan Siregar; Elda Nazriati (Dinamika Lingkungan Indonesia, 2019)
Healthcare development contributing positive outcome on public health status, but on the other side, medical waste existence become a troublesome as long as increased medical healthcare quantity particularly private dental healthcare. The amount of improperly managed medical wastes become accumulated and causing widespread pollution. The roblem of this study is improperly managed medical waste getting more increased causing widespread pollution. Even though 15-25 % of this contamination were categorized as hazardous waste, the risk is much greater. The purpose of this study was to analyze the number and types of private healthcare medical waste and its potential pollution. This study used descriptive qualitative with interviews and observations after conducting a survey of calculating the number and identification of medical waste types produced by private dental healthcare in Pekanbaru. The results showed 69% of infectious, 27% toxic, and 4% radioactive wastes. The presence of this medical waste has the potential to polluting water and soil environment, triggering health problems for health workers and high risk communities, and disrupting social and economic aspects of residents at nearby waste disposal. It is recommended that private dental healthcare to reduce generated medical wastes and to use safe and eco-friendly materials and tools for dental and oral care.